Resilient Adult Daughters of Abused Women: Turning Pain Into Purpose. (May 2020) - Anderson, Kim M.; Bernhardt, Christina
Through the use of purposive sampling and the grounded theory method, this qualitative study delineates factors that promote adaptation and end family patterns of violence and dysfunction in the case of resilient adult daughters of abused women ( N = 29). Coping processes included distancing from the family, seeking understanding and acceptance, and finding meaning and purpose. Motivating factors included learning what not to do from their families and breaking the cycle of violence and dysfunction from occurring in their adult lives. We learn how daughters of abused women may create a life informed, rather than directed, by their childhood adversity.